2019
DOI: 10.2478/psicolj-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Mapping of Auditory Loudness: Loud is High, but Quiet is not Always Low

Abstract: Although the perceptual association between verticality and pitch has been widely studied, the link between loudness and verticality is not fully understood yet. While loud and quiet sounds are assumed to be equally associated crossmodally with spatial elevation, there are perceptual differences between the two types of sounds that may suggest the contrary. For example, loud sounds tend to generate greater activity, both behaviourally and neurally, than quiet sounds. Here we investigated whether this differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
(101 reference statements)
3
2
0
1
Order By: Relevance
“…Other three-way interactions were not significant (all ps>0.4); neither was the four-way interaction (p > 0.07). Thus, critically, loudness showed no cross-modal correspondence effect, confirming previous result on its instability ( Puigcerver et al, 2019 ). Most importantly, the pitch-space effect disappeared when it became task-irrelevant, suggesting non-automaticity of the cross-modal correspondence.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Other three-way interactions were not significant (all ps>0.4); neither was the four-way interaction (p > 0.07). Thus, critically, loudness showed no cross-modal correspondence effect, confirming previous result on its instability ( Puigcerver et al, 2019 ). Most importantly, the pitch-space effect disappeared when it became task-irrelevant, suggesting non-automaticity of the cross-modal correspondence.…”
Section: Resultssupporting
confidence: 88%
“…However, when the attention was directed to the loudness, the pitch-space integration disappeared. Furthermore—and importantly—the study revealed no loudness-space correspondence regardless of the task (not even in the loudness identification condition), which confirms earlier observations of low reliability of audiovisual effects involving loudness and vertical space ( Puigcerver et al, 2019 ). The latter may, in turn, stem from the absence of ecological/environmental bases for such a correspondence to arise, unlike the ecologically grounded pitch-location associations ( Parise et al, 2014 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Так, слова «высокий» и «низкий» описывают и частоту звука, и пространственную высоту, воспринимаемую зрительно (Spence, 2020). Дру гими словами, судя по полученным ранее данным, эффект аудиовизуального соответствия нестабилен и, возможно, связан с устройством речевого опыта человека (Spence, 2011;Puigcerver et al, 2019). В пользу такого вывода говорят и данные о том, что носители разных языков различаются по своим пространственно-временным ассоциациям: например, в голландском языке, как и в русском, используют метафору высоты тона, а в турецком -метафору его толщины («тонким» называют высокий тон звука, а «толстым» -низкий).…”
Section: Discussionunclassified